Inhibition of neutrophil migration by a selective inhibitor of matrix metalloproteinase: analysis by intravital microscopy - T. Oda; M. Katori; K. Hatanaka; Y. Nagai (Hindawi Limited, 1995)
Observation of the microcirculation of the hamster cheek pouch by intravital microscopy revealed five steps of neutrophil migration from the venules after topical application of leukotriene B4 to the microvasculature: rolling along the venular wall (Step 1), adhesion to it (Step 2), disappearance from the vascular lumen (Step 3), presence between the endothelial cells and the subendothelial basement membrane (Step 4) and passage through the basement membrane (Step 5). The present study was performed to examine whether a metalloproteinase inhibitor inhibits neutrophil migration at any of the above five steps. Chymostatin and leupeptin did not inhibit any of these five steps. In contrast, FN-439, a selective inhibitor of matrix metalloproteinase, reduced the number of neutrophils in the perivascular space without affecting Steps 1 to 3. It was concluded that neutrophils may use metalloproteinase (collagenase/gelatinase) to penetrate the subendothelial basement membrane.